2017
DOI: 10.1111/all.13186
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐activated receptor‐2 suppresses interleukin (IL)‐10 expression in B cells via upregulating Bcl2L12 in patients with allergic rhinitis

Abstract: Activation of PAR2 inhibits the expression of IL-10 in B cells, which can be reversed by treating B cells with Bcl2L12 shRNA-carrying liposomes. The data suggest that regulation of Bcl2L12 may be a novel approach in the treatment for AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…It was lately found that Bcl2L12 was also involved in the development of other types of cancer with its anti‐apoptotic activities . Further reports indicate that Bcl2L12 is associated with the immune deregulation . The present study has added novel information to this study field that Bcl2L12 regulates CD4 + T cell activities by compromising the apoptosis machinery to induce defects of apoptosis in CD4 + T cells.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…It was lately found that Bcl2L12 was also involved in the development of other types of cancer with its anti‐apoptotic activities . Further reports indicate that Bcl2L12 is associated with the immune deregulation . The present study has added novel information to this study field that Bcl2L12 regulates CD4 + T cell activities by compromising the apoptosis machinery to induce defects of apoptosis in CD4 + T cells.…”
Section: Discussionmentioning
confidence: 62%
“…20 Further reports indicate that Bcl2L12 is associated with the immune deregulation. 12,13 The present study has added novel information to this study field that Bcl2L12 regulates CD4 + T cell activities by compromising the apoptosis machinery to induce defects of apoptosis in CD4 + T cells. On the other hand, the defects of apoptosis in CD4 + T cells may be also a result of Th2 polarization because IL-5 can increase the expression of Bcl2L12 in CD4 + T cells.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The activation of protease-activated receptor (PAR)-2 on B cells inhibits IL-10 expression in peripheral B cells via upregulating Bcl2-like protein-12 (Bcl2L12). 45 Novel therapeutic candidates for the treatment of AR have been developed that compete with Bcl2L12 and restore IL-10 production, as recently demonstrated in a mouse model treated with Bcl2L12 shRNA liposomes ( Figure 2). Forkhead box protein-3 (Foxp3) is a key transcription factor of T regulatory (Treg) cells implicated in immune tolerance.…”
Section: Novel Hi G Hli G Hts On Mechanis Ms Of Allerg I C D Is E Amentioning
confidence: 97%
“…48 It was reported that activation of protease-activated receptor (PAR)-2 promotes the suppression of IL-10 in B cells, which can be inhibited by treating B cells with Bcl2-like protein 12 (Bcl2L12) shRNA-carrying liposomes. 53 These data suggest that regulation of Bcl2L12 may be a novel approach in the treatment for AR.…”
mentioning
confidence: 90%